(Over)-stylizing experimental findings and theorizing with sweeping generality - Werner Güth; Hartmut Kliemt; Maria Vittoria Levati (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
Human decision making is a process guided by different and partly competing mo-tivations that can each dominate behavior and lead to different effects depending on strength and circumstances. Over-stylizing neglects such competing concerns and context-dependence, although it facilitates the emergence of elaborate general theories. We illustrate by examples from social dilemma experiments and inequality aversion theories that sweeping empirical claims should be avoided.
Keywords: A11; D63; D70; 330; Context-dependent preferences; experimental economics; equity theo-ries; Verhaltensökonomik; Präferenztheorie; Gefangenendilemma; Gerechtigkeit; Test